Association of Blood Pressure With Outcomes in Acute Stroke Thrombectomy. Issue 3 (March 2020) - Malhotra, Konark; Goyal, Nitin; Katsanos, Aristeidis H.; Filippatou, Angeliki; Mistry, Eva A.; Khatri, Pooja; Anadani, Mohammad; Spiotta, Alejandro M.; Sandset, Else Charlotte; Sarraj, Amrou; Magoufis, Georgios; Krogias, Christos; et al.
Abstract : Limited data exist evaluating the effect of blood pressure (BP) on clinical outcomes among patients with acute ischemic stroke with large vessel occlusion treated with mechanical thrombectomy (MT). We sought to evaluate the association of BP levels on clinical outcomes among patients with acute ischemic stroke with large vessel occlusion treated with MT. Studies were identified that reported the association of systolic BP (SBP) or diastolic BP levels before, during, or after MT on the outcomes of patients with acute ischemic stroke treated with MT. Unadjusted and adjusted analyses of studies reporting odds ratios (ORadj ) per 10 mm Hg BP increment were performed. Our analysis included 25 studies comprising 6474 patients. Higher pre-MT mean SBP ( P =0.008) and post-MT maximum SBP ( P =0.009) levels were observed in patients who died within 3 months. Patients with 3-month functional independence were noted to have lower pre-MT ( P <0.001) and post-MT maximum SBP levels ( P <0.001). In adjusted analyses, increasing post-MT maximum SBP and diastolic BP levels were associated with 3-month mortality (ORadj, 1.19 [95% CI, 1.00–1.43]; I 2 =78%, P value for Cochran Q test: 0.001) and symptomatic intracranial hemorrhage (ORadj, 1.65 [95% CI, 1.11–2.44]; I 2 =0%, P value for Cochran Q test: 0.80), respectively. Increasing pre- and post-MT mean SBP levels were associated with lower odds of 3-month functional independence (ORadj, 0.86 [95% CI, 0.77–0.96]; I 2 =18%, P value for Cochran Q test: 0.30) and (ORadj, 0.80 [95% CI, 0.72–0.89]; I 2 =0%, P value for Cochran Q test: 0.51), respectively. In conclusion, elevated BP levels before and after MT are associated with adverse outcomes among patients with acute ischemic stroke with large vessel occlusion. Abstract : Supplemental Digital Content is available in the text.